2012
DOI: 10.1159/000342418
|View full text |Cite
|
Sign up to set email alerts
|

Amniopatch Treatment for Spontaneous Previable, Preterm Premature Rupture of Membranes Associated or Not with Incompetent Cervix

Abstract: Objective: We reviewed women with previable spontaneous premature rupture of membranes (sPPROM) in whom an amniopatch was performed and compared their pregnancy outcomes with a conservative management group. Methods: Amniopatch, an amnioinfusion of autologous platelet concentrate followed by cryoprecipitate, was performed in 7 women with sPPROM diagnosed at 17–23 weeks’ gestation, including one twin pregnancy. Three patients had incompetent cervices and the other 4 patients had sPPROM without incompetent cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…For these reasons, previous studies have found that the amniopatch procedure in sPPROM is far less effective . We reviewed the available literature to find cases of sPPROM treated with amniopatch but the treatment was only successful in a few cases [11,15,19]. Kwak et al reported in his study that amniopatch treatment in spontaneous ruptures was successful in 1 out of 7 cases (14.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, previous studies have found that the amniopatch procedure in sPPROM is far less effective . We reviewed the available literature to find cases of sPPROM treated with amniopatch but the treatment was only successful in a few cases [11,15,19]. Kwak et al reported in his study that amniopatch treatment in spontaneous ruptures was successful in 1 out of 7 cases (14.3%).…”
Section: Discussionmentioning
confidence: 99%
“…All except one were born prematurely and one had a mild disability. Other studies reported lower rates of complet healing of membranes with spontaneous rupture (11-14.3 %) [19][20][21]. Contino et al and Ferianec both reported two successful cases delivered at 27 weeks [12] and 33 weeks of gestation [15], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another 100 ml of normal saline is then instilled to achieve the optimal (> 5 cm) deepest pocket of the AF bag. Theoretically, the platelet/cryoprecipitate plug may seal the amniotic membranous defect by artificial platelet activation and fibrin adhesion at the site of the rupture, forming a 'white' coagulum as a plug 123,124,126,133 . In our analysis, the overall perinatal survival rate was highest (61.4%) after treatment with AP.…”
mentioning
confidence: 99%
“…This technique is basically performed in the case of iPPROM. In sPPROM cases, the AP predominantly fails, usually because of infection 133 . The membrane defects after needle-based procedures or fetoscopy are usually well demarcated and relatively small, and the needles or trocars are usually inserted into the uterine cavity under sterile circumstances.…”
mentioning
confidence: 99%
See 1 more Smart Citation